Battery Electric Bus Selection Based on Entropy Weight Method and Road Operation Test: Using Nanjing Bus Company as an Example. (10th August 2022) - He, Zhixia
Abstract : Before putting battery electric buses into actual daily operations, the selection of buses is of great importance to the bus companies and the improvement of energy efficiency. Based on multi-dimension big data provided by the Nanjing Bus Company and by adopting the entropy weight method and road operation test, this paper presented an objective method for the selection of battery electric bus. Each of these four enterprises, BYD, Kaiwo, Yinlong, and Jiankang which were commonly seen in the Chinese market, provided two types of battery electric buses. Four different routes were selected for the road test and collected over 50 days of daily operation test data. In order to reflect all aspects of the vehicle performance, eight indexes which had been considered and designed comprehensively were classified into three categories: reliability, economy, and security. Together with the road operation data, an evaluation system based on the bus's daily operation performance was established through the entropy weight method. Assessing results showed that battery electric bus with better performance usually had a total evaluation score over 0.69. Generally, electric buses with high scores on one route also had higher scores on all the other routes, such as brand D. But, on unimpeded routes, results may differ, for example, in route 134 W, 10-meter buses of brand B ranked first. In contrast to earlier studies, the selection result obtained by this method was more objective and intuitional, which was also consistent with the actual scenario. The selection process indicates that this method is highly practical and can be easily carried out. Therefore, we can assume that the proposed method can evaluate the actual operation state of battery electric buses and provides a new selection way.